Who Settles for Less? Subjective Dispositions, Objective Circumstances, and Housing Satisfaction - Tomaszewski, W; Perales, Francisco; Perales, F; Tomaszewski, Wojtek (My University, 2013)
In recent years there has been growing interest in individuals’ self-perceptions of their wellbeing on the grounds that these complement well-established objective indicators of welfare. However, individuals’ assessments depend on both objective circumstances and subjective, idiosyncratic dispositions, such as aspirations and expectations. We add to the literature by formulating a modelling strategy that uncovers how these subjective dispositions differ across socio-demographic groups. This is then tested using housing satisfaction data from a large-scale household panel survey from Australia. We find that there are significant differences in the way in which individuals with different characteristics rate the same objective reality. For instance, male, older, migrant, and Indigenous individuals rate equal housing conditions more favourably than female, younger, Australian-born, and non-Indigenous individuals. These findings have important implications for how self-reported housing satisfaction, and wellbeing data in general, are to be used to inform evidence-based policy.
Keywords: Health -- Wellbeing; Housing -- Conditions; Satisfaction; Housing; Health and wellbeing; Housing; Satisfaction; Health; Conditions; Wellbeing; Health and wellbeing